Inhibitory Activity of Marine Sponge-Derived Natural Products against Parasitic Protozoa - Deniz Tasdemir; Reto Brun; Marcel Kaiser; Bilge Şener; Ilkay Orhan (Marine Drugs, 2010)
In this study, thirteen sponge-derived terpenoids, including five linear furanoterpenes: furospinulosin-1 (1), furospinulosin-2 (2), furospongin-1 (3), furospongin-4 (4), and demethylfurospongin-4 (5); four linear meroterpenes: 2-(hexaprenylmethyl)-2-methylchromenol (6), 4-hydroxy-3-octaprenylbenzoic acid (7), 4-hydroxy-3-tetraprenyl-phenylacetic acid (8), and heptaprenyl-p-quinol (9); a linear triterpene, squalene (10); two spongian-type diterpenes dorisenone D (11) and 11β-acetoxyspongi-12-en-16-one (12); a scalarane-type sesterterpene; 12-epi-deoxoscalarin (13), as well as an indole alkaloid, tryptophol (14) were screened for their in vitro activity against four parasitic protozoa; Trypanosoma brucei rhodesiense, Trypanosoma cruzi, Leishmania donovani and Plasmodium falciparum. Cytotoxic potential of the compounds on mammalian cells was also assessed. All compounds were active against T. brucei rhodesiense, with compound 8 being the most potent (IC50 0.60 μg/mL), whereas 9 and 12 were the most active compounds against T. cruzi, with IC50 values around 4 μg/mL. Compound 12 showed the strongest leishmanicidal activity (IC50 0.75 µg/mL), which was comparable to that of miltefosine (IC50 0.20 µg/mL). The best antiplasmodial effect was exerted by compound 11 (IC50 0.43 µg/mL), followed by compounds 7, 10, and 12 with IC50 values around 1 µg/mL. Compounds 9, 11 and 12 exhibited, besides their antiprotozoal activity, also some cytotoxicity, whereas all other compounds had low or no cytotoxicity towards the mammalian cell line. This is the first report of antiprotozoal activity of marine metabolites 1–14, and points out the potential of marine sponges in discovery of new antiprotozoal lead compounds.